Analisis Dampak Kehadiran Pertashop Pada Penjualan Bensin Eceran Di Warung Kelontong Di Kecamatan Trenggalek, Kabupaten Trenggalek - Muslikah, Fitri Erna; Nurlaely, Nurlaely; Rahayu, Budi; Sustiyatik, Enni (Jurnal Ilmiah Raflesia Akuntansi, 2023)
— This study aims to determine the impact of the presence of Pertashop retail outlets on the sales of gasoline at local convenience stores in Trenggalek District, as well as the factors and strategies implemented in response to these changes. This research is a descriptive qualitative study. Field data indicate that the presence of Pertashop has a negative impact (viewed as competition) on convenience stores as micro-enterprises (UMKM) located within 1 kilometer of Pertashop. On the other hand, convenience stores located more than 1 kilometer away view Pertashop positively, as it becomes a source for purchasing Pertamax gasoline in bulk. However, overall sales changes are mainly influenced by the general increase in gasoline prices (leading Pertamax users to switch to cheaper gasoline) and the occurrence of major events in the surrounding area. To cope with these changes, the most common strategy is to display gasoline racks at the front (roadside) to make them easily visible from the road. Most stores have already put up signs indicating they sell gasoline, but offering various sizes and providing lighting is still not widely adopted by these business owners.